KESENIAN LANGGIR BADONG KREASI ADE SUARSA DI SANGGAR ETNIKA DAYA SORA KOTA BOGOR - Arnetha Deyananda, - (2022)
Creativity is an ability that reflects fluency, flexibility (flexibility), and originality in thinking, as well as the ability to elaborate (develop, enrich, detail), an idea or ideas. Creativity can be poured into various forms such as appearance, motion, sound, product, or language. This study aims to determine the concept of creating, performing and working onmusic Langgir Badong's. Langgir Badong is an art from Bogor City which has its own characteristics and charms. The overall uniqueness of Langgir Badong includes the combination of harmonious and complex musical instrument playing with dynamic movements, making Langgir Badong a unique and attractive performance that can captivate the entire audience. In this study, qualitative methods were used, namely research methods based on philosophy which are commonly used to examine the condition of natural objects that make researchers the key instrument. The result of this research is to know how the creativity of Ade Suarsa in creating Langgir Badong in the Daya Sora Ethnic Studio, Bogor City.